Individuals carrying the HLA-B*15 allele exhibit favorable responses to COVID-19 vaccines but are more susceptible to Omicron BA.5.2 and XBB.1.16 infection - Meng, Lingxin; Pan, Yue; Liu, Yueping; He, Rui; Sun, Yuting; Wang, Chenhui; Fei, Lei; Zhu, Airu; Wang, Zhongfang; An, Yunfei; Wu, Yuzhang; Diao, Bo; et al. (Frontiers in Immunology, 2024)
CoV-2 invasion, nevertheless, Omicron variants still successfully cause breakthrough infection, and the underlying mechanisms are poorly understood.. Sequential blood samples were continuously collected at different time points from 252 volunteers who were received the CanSino Ad5-nCoV (n= 183) vaccine or the Sinovac CoronaVac inactivated vaccine (n= 69). The anti-SARS-CoV-2 prototype and Omicron BA.5.2 as well as XBB.1.16 variant neutralizing antibodies (Nab) in sera were detected by ELISA. Sera were also used to measure pseudo and live virus neutralization assay. The associations between the anti-prototype Nab levels and different HLA-ABC alleles were analyzed using artificial intelligence (AI)-deep learning techniques. The frequency of B cells in PBMCs was investigated by flow cytometry assay (FACs). Results. Individuals carrying the HLA-B * 15 allele manifested the highest concentrations of anti-SARS-CoV-2 prototype Nab after vax administration. Unfortunately, these volunteers are more susceptible to Omicron BA.5.2 breakthrough infection due to their sera have poorer anti-BA.5.2 Nab and lower levels of viral neutralization efficacy. FACs confirmed that a significant decrease in CD19 + CD27 + RBD + memory B cells in these HLA-B * 15 population compared to other cohorts. Importantly, generating lower concentrations of cross-reactive anti-XBB.1.16 Nab post-BA.5.2 infection caused HLA-B * 15 individuals to be further infected by XBB.1.16 variant. Conclusions. Individuals carrying the HLA-B * 15 allele respond better to COVID-19 vax including the CanSino Ad5-nCoV and the Sinovac CoronaVac inactivated vaccines, but are more susceptible to Omicron variant infection, thus, a novel vaccine against this population is necessary for COVID-19 pandemic control in the future.